India's export trends and the prospects for self-sustained growth - Singh, Manmohan (Oxford : Clarendon Press, 1964)
The sluggishness of India's export earnings since 1952 is a well observed fact. However, no comprehensive analysis of the casual factors at work is available so far. The present work tries to fill this gap.
Includes bibliographical footnotes and index.
ne 22/01/2019
Loans
Keywords: Developing countries--Foreign economic relations; Tariff preferences--Developing countries; Economic development--Developing countries; India